Intimate Partner Violence as a Manifestation of Relational Vulnerability in Karen Rose’s Don’t Tell - Nenin Astiti Ayunda (Linguistics and ELT Journal, 2020)
Violence against women is gender-related violence manifesting the men power over women. In a patriarchal society, women are inferior within hierarchical gender relations. This study is made to disclose the incidence of domestic violence against women that shows how vulnerable women are in a relationship, especially the married one. The result shows that status of a woman, housewife and mother as described by the main character in the novel is considered subordinate and susceptible to multioppression. Extremely, the marriage is such detention for her to be an independent individual. When domestic violence happens toward a wife perpetrated by her husband, between fear and prevalence assumption, society is soundless. This violence is a manifestation of relational vulnerability.